(NiSTORIQ MEDICINYs (Nu^EBNIKs - (Nt(B.(Ns(B.(NsOROKINAs ((NmOSKWAs "(NaKADEMIQ(B"s, 2008)
(NiSTORIQ MEDICINY PREDSTAWLENA W KONATEKSTE ISTORII NAU^NOGO ZNANIE W CELOM(B.s
Keywords: (NiSTORIQ MEDICINYs